Fact and fake news: knowledge of Nursing student facing the COVID-19 pandemic (Research, Society and Development, 2021)
The COVID-19 pandemic brought changes in daily life, isolation and social distancing increased the search for information in the media and social networks. Fake news generated confusion and insecurity. Health professionals and students play an important role in clarifying the population's doubts. To assess the knowledge of students from the Nursing Course at the Federal University of Maranhão in relation to the COVID-19 pandemic, an electronic questionnaire covering facts and fake news was applied. We found that 90.8% stated that fake news may have contributed to increase the transmission of the SARS-COV2 virus. Television newspapers, news sites and scientific articles were the media used, with 81.8%, 72.7% and 68.2%, respectively, and 40% using social media. Students considered fake news: 86.4% the hypothesis that the virus might have been created in the laboratory, 100% that the virus might be the result of the electromagnetic influence of the data network, 95.5% that the use of infrared thermometers causes brain damage,100 % that drugs such as Chloroquine, Ivermectin and Azithromycin can be used for both prevention and treatment and 100% that those who have already had COVID-19 do not need to be vaccinated. As an intervention, an online lecture was held, identifying the harmful points and susceptible to false disclosures, followed by a post-intervention questionnaire. We found that 100% of students responded that they were able to differentiate fake news from true information, highlighting the importance of reliable sources and the transmission of true guidance to the population.